Asia-Pacific consensus statement on integrated 24-hour activity guidelines for the early yearsResearch in context - Benny Kai Guo Loo; Anthony Okely; Rachael Taylor; Rachel Novotny; Pujitha Wickramasinghe; Falk Müller-Riemenschneider; Gade Waqa; Aman Pulungan; Satoshi Kusuda; Kok Hian Tan (Elsevier, 2023)
Summary: Background: Early childhood is a vital period for development and growth. Promoting beneficial lifestyle behaviours in early childhood can help optimise children's health, development and learning, shape their behaviours in adulthood and offer the best protection against future non-communicable diseases (NCDs). In the Asia-Pacific region, NCDs are significant causes of healthcare burden and mortality. Furthermore, there is also a high prevalence of adverse metabolic risk factors and unhealthy lifestyle behaviours among these children. Method: Representatives from 19 Asia-Pacific nations and/or jurisdictions developed a consensus statement on integrated 24-hour activity guidelines for the early years using the GRADE-ADOLOPMENT framework. Findings: These guidelines apply to all infants, toddlers and pre-schoolers below 5 years of age. The guidelines aim to provide a holistic and practical approach to lifestyle activities by framing physical activity, sedentary behaviour and sleep within a 24-hour period. Dietary patterns were included as they play an integral role in metabolic health and energy balance. Interpretation: Aligned with the World Health Organization's Global Action Plan for the Prevention and Control of NCDs through health promotion interventions in early life, through cultivating healthy lifestyle behaviours in the children's early years, we aim to provide children with the best start in life and reduce the burden of future NCDs in the Asia-Pacific region. Funding: Funded by Integrated platform for research in advancing metabolic health outcomes of women and children